The Effect Of Work Culture On The Improvement Of Work Performance Of Dispora Employees Lamongan Regency - Siddiq Siddiq; Iswanto Iswanto (Trunojoyo University of Madura, 2019)
Work culture is a philosophy as values into the nature, habits, and the driving force that is shared by every individual in the working environment of an organization. This study aims to determine whether the work culture, discipline, openness, and cooperation has partially and simultaneously influence on work performance of Dispora employees. Based on the background and purpose of the study above it can be drawn a conclusion that is allegedly working culture that consists of a variable discipline, openness and cooperation and simultaneous partial effect on work performance. Allegedly discipline variable most dominant influence on the performance of Dispora employees. Data used in the study consisted of: primary data and secondary data. Further data collection techniques by using observation, documentary and questionnaire. Data analysis methods: Test Validity, Reliability Testing , Regression , Correlation , Coefficient of Determination , t Test , and Test F. From the test results obtained t count variable t discipline ( X1 ) 8.694 1.678 ≥ t table , openness variable ( X2 ) 4,656 ≥ t table 1,678 and variable cooperation ( X3 ) 7.498 1.678 ≥ t table. So it can be concluded that the discipline variable ( X1 ) , openness ( X2 ) and cooperation ( X3 ) partially significant effect on job performance ( Y ) employees Dispora Lamongan . ANOVA table F count equal to 233.739 ≥ f. The table is 2.81 means that the variable discipline, openness, and cooperation simultaneously significant effect on job performance . Y = 1.179 + 1,340X1 + 0,578X2 + 0,783X3. Judging from discipline variable regression coefficient of 1.340 has the greatest value compared with other variable regression coefficient (openness and cooperation). Thus it can be concluded that the most dominant factor influencing performance is variable discipline. Based on the above analysis of the research results it can be deduced that the variable discipline , openness , and cooperation has a significant influence on the performance of partially or simultaneously , and it can be seen that the variable most dominant discipline on job performance. Employee discipline should be put forward by the management office. Based on research conducted by multiple factors evident that discipline is regarded as an influential factor on the performance of the Dispora office.